2008
DOI: 10.5123/s1981-81142008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Restingas do litoral amazônico, estados do Pará e Amapá, Brasil

Abstract: Resumo: Na Amazônia brasileira, as restingas ocupam uma área de aproximadamente 1.000 km 2 , correspondendo a menos de 0,1% dos demais tipos de vegetação ocorrentes na região. O presente estudo tem por objetivo caracterizar as restingas dos estados do Pará e Amapá, com base em informações florísticas (incluindo o primeiro checklist para a Amazônia), fisionômicas e geomorfológicas, e estabelecer uma classificação de padrões de ocorrência deste tipo de vegetação litorânea na costa amazônica. Para tal, foram inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
26

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 8 publications
5
33
0
26
Order By: Relevance
“…However, in spite of this floristic likeness and the fact these areas are geographically close, these three floras show distinct species compositions that reflect unique abiotic and biotic interactions (Santos-Filho et al 2013). Amaral et al (2008) noticed differences between restinga families' species richness throughout the Amazonian coast (Fabaceae, Cyperaceae, Poaceae, Rubiaceae, Myrtaceae and Asteraceae) and common families in the Atlantic Forest (families cited above) that were found in restinga sites along the coast of Rio de Janeiro State (Scarano 2002). A good example is Eriocaulaceae, among the ten families with greatest number of species along the coast of the Amazon region (Amaral et al 2008 and present study), but was not listed even among the 20 most important families in a survey undertaken in Rio de Janeiro (Araujo 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in spite of this floristic likeness and the fact these areas are geographically close, these three floras show distinct species compositions that reflect unique abiotic and biotic interactions (Santos-Filho et al 2013). Amaral et al (2008) noticed differences between restinga families' species richness throughout the Amazonian coast (Fabaceae, Cyperaceae, Poaceae, Rubiaceae, Myrtaceae and Asteraceae) and common families in the Atlantic Forest (families cited above) that were found in restinga sites along the coast of Rio de Janeiro State (Scarano 2002). A good example is Eriocaulaceae, among the ten families with greatest number of species along the coast of the Amazon region (Amaral et al 2008 and present study), but was not listed even among the 20 most important families in a survey undertaken in Rio de Janeiro (Araujo 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Amaral et al (2008) noticed differences between restinga families' species richness throughout the Amazonian coast (Fabaceae, Cyperaceae, Poaceae, Rubiaceae, Myrtaceae and Asteraceae) and common families in the Atlantic Forest (families cited above) that were found in restinga sites along the coast of Rio de Janeiro State (Scarano 2002). A good example is Eriocaulaceae, among the ten families with greatest number of species along the coast of the Amazon region (Amaral et al 2008 and present study), but was not listed even among the 20 most important families in a survey undertaken in Rio de Janeiro (Araujo 2000). Moreover, floristic surveys undertaken in northeastern Brazil often show the family Eriocaulaceae appearing among the 20 richest families (Sacramento et al 2007;Almeida Jr. et al 2009;Cantarelli et al 2012), or completely absent in the list of species Santos-Filho et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSM is described for Crispim Beach only (Costa-Neto 1999) but it is possible that this formation was not clearly separated from other types of marsh vegetation by other authors. Occurrence of PWM was documented for Crispim and Algodoal (Amaral et al 2008); the remaining formations have been observed along the entire coastline.…”
Section: Resultsmentioning
confidence: 97%
“…The species assemblages at the remaining sites within the study area were characterized by "rapid assessment"-type surveys (Lisboa et al 1993, Bastos et al 2002. Amaral et al (2008) present a check-list of species reported at 10 sites along the Brazilian Amazon coast but do not consider the more recent studies at Vila Bonifácio (Silva et al 2007, Santos 2008, Silva 2008. A small number of studies provide local taxonomic keys for certain groups (Turneraceae: Vicente et al 1999;Poaceae: Rocha et al 2001a herbaceous species found at a specific site (Amaral 1997, Costa-Neto 1999, Silva 2008.…”
Section: Resultsmentioning
confidence: 99%